If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + 9 = 2z + -3 Reorder the terms: 9 + 5z = 2z + -3 Reorder the terms: 9 + 5z = -3 + 2z Solving 9 + 5z = -3 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 9 + 5z + -2z = -3 + 2z + -2z Combine like terms: 5z + -2z = 3z 9 + 3z = -3 + 2z + -2z Combine like terms: 2z + -2z = 0 9 + 3z = -3 + 0 9 + 3z = -3 Add '-9' to each side of the equation. 9 + -9 + 3z = -3 + -9 Combine like terms: 9 + -9 = 0 0 + 3z = -3 + -9 3z = -3 + -9 Combine like terms: -3 + -9 = -12 3z = -12 Divide each side by '3'. z = -4 Simplifying z = -4
| p/8+5=9 | | 8x-2=4x+14 | | 98-3x=24x+23 | | 4x-8=28-2x | | 500-25x=-250+50x | | 7-x+3x-3-8x= | | -5(x+4)=-6x | | s=2*2.14rh | | -3(7n-4)+4n= | | (3y+1)+25= | | 7.7(x-2)=-0.3x+40.6 | | -81=-9k | | 10x-5x=5 | | -8=a+3 | | -5(n-1)-4h= | | 1x^2-3x+2=0 | | -2(9p+5)= | | y=.75x+2 | | 6(d+1)= | | 6(2x+3)=-9 | | 3y-7+5y-9= | | -3(x-5)=3(x-1) | | -6(2+3)+52= | | 16y-22y= | | A=1/2*10(6+15) | | x^2=-5 | | x^2-25=2x | | 5(2+x)+2x=20-(2x+6) | | 3x-6x+2= | | x-7x+29=0 | | 10-8x=86-22x | | 0.8x+.18=.3(x+.2) |